Management challenges to implementing agile processes in traditional development organizations - and Boehm, B.; Turner, R. (IEEE Software, 2005)
Discussions with traditional developers and managers concerning agile software development practices nearly always contain two somewhat contradictory ideas. They find that on small, stand-alone projects, agile practices are less burdensome and more in tune with the software industry's increasing needs for rapid development and coping with continuous change. Managers face several barriers, real and perceived, when they try to bring agile approaches into traditional organizations. They categorized the barriers either as problems only in terms of scope or scale, or as significant general issues needing resolution. From these two categories, we've identified three areas - development process conflicts, business process conflicts, and people conflicts - that we believe are the critical challenges to software managers of large organizations in bringing agile approaches to bear in their projects.
Keywords: Aerospace engineering; Aerospace materials; Agile methods; Agile software development; Automatic testing; Business processes; Computer industry; DP industry; Programming; Project management; Refining; Software engineering; Software management; Software systems; development process conflicts; process integration; software development management; software industry; systems engineering; traditional development organizations